Critical investigation: transversal reason, discursive ethics and democracy (Revista Electrónica REDINE, 2020)
The intent of the essay is to reflect on transversal reason, discursive ethics and democracy as constitutive aspects of being and doing critical research in the social sciences. It is assumed that thought and action is an indissoluble binomial in the search for real changes and transformations, constantly fed back by reflection. It considers the reason as transversal, because it shelters modes of operating by transits. This refers to the creation of transitive connections between different complexes, such as reality. Unique and plural thought come together, generating "plural unity" and weak thought. Discursive ethics, as a set of theories proposed for community praxis, values ​​argumentation and recognizes the legitimacy of the other. This is the foundation of a solid democracy built by everyone from common spaces.In addition to this, investigating to change requires introducing changes that demand, speaking from the truth, believing, listening to ourselves, reflecting, expressing our reason; arguing. Key words: Critical investigation
Keywords: Critical invcestigation; transversal reason; discursive ethics and democracy